Class-reconfigurable RF power amplifier using continuously tunable harmonic output matching network - Mendoza, Genedyn Gems S.; Purisima, Miguel Carlo L. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Single transistor RF power amplifiers (RF PA) are usually fixed to its designed performance, limiting its adaptability between different wireless standards. To avoid using different amplifiers for different applications, there is an increasing demand for RF PAs to become more flexible to allow inter-operability between these applications. The potential improvement of PA flexibility to multi-standard operations at a fixed frequency band is studied through the design and implementation of a class-reconfigurable RF PA that can enable a Linear Mode (LM) for systems involving high PAPR signals, and a High Efficiency Mode (HEM) for systems which can tolerate amplifier nonlinearity. Operating mode is set by changing the bias and independently controlling the fundamental and 2nd harmonic output impedances through the continuously tunable harmonic OMN. Class reconfigurability of the designed RF PA was verified through simulations and actual performance. Hardware measurements across 920-960 MHz showed that the designed PA at LM has better linearity with higher PI d B of 36.83-38.05 dBm, compared to 32.8-34.6 dBm at HEM, and IMD3 levels <-30 dB for average output power up to 33.2 dBm , compared to only up to 25.38 dBm at H EM, with -10.55 to -25.55 dB IMD3 improvement. At HEM, the PA is significantly more efficient than at LM for output power<37 dBm, with >20% PAE improvement from 30-37 dBm, and 63.4% peak PAE at 37 dBm, compared to 57.56% peak PAE at 39.4d8m for LM. The study was able to provide a better understanding of the design of not only CRRFPAs. but also tunable amplifiers. in general.
Thesis (M.S. Electrical Engineering)--University of the Philippines Diliman
Keywords: Power amplifiers